Effectiveness of Cobalt-Doped Biochar Derived from Durian Shell for Degradation of Rhodamine B - Trinh, Anh Mai Hoang; Le, Thinh Phu; Tran, Khoi Anh; Do, Nga Hoang Nguyen; Le, Kien Anh; Tran, Viet Tan; Le, Phung Kim (Indonesian Journal of Chemistry, 2025)
The global discharge of dye-contaminated effluent into the environment has garnered considerable public attention, and removing the organic pollutants from wastewater is of great importance. Durian shell, a major by-product of Asia countries, is one of the primary causes of environmental issues. To address these current issues, the development of efficient and eco-friendly biomass-derived catalysts that activate advanced oxidation processes (AOP) stands out as a crucial technology for treating organic pollutants in water. In this study, cobalt-doped biochar composites (CoC-n) were synthesized using solvothermal and calcination techniques, with durian shell biomass serving as the precursor material. The obtained CoC-n treated under various calcination temperatures analyzed via SEM, EDS, XRD, and FTIR techniques, which were used for efficient peroxymonosulfate (PMS) activation for up to 92% and 58.98–74.30% RhB (25  and 75 mg/L, respectively) degradation in 30 min. The quenching test performed on the CoC-350/PMS system revealed that RhB degradation involves sulfate (SO4•−), hydroxyl (OH•), and singlet oxygen (1O2) in RhB degradation, with SO4•− and 1O2 being the primary components. The cobalt-doped biochar from durian shells is considered a novel and promising candidate for the eradication of dye-contaminated effluent applications.